Jobs for the'90s - Ellis, Jack. (Pleasantville, N.Y : Pleasantville Media, 1987)
Helps students focus their career objectives on the most promising job fields for the 1990s. Uses the Holland hexagon to help viewers match their job skills and abilities to career categories described.
pt.1. Where you fit in - pt.2. The doers and the thinkers - pt.3. The creators and the helpers - pt.4. The persuaders and the organizers.
Keywords: Occupations -- Forecasting; Professions -- Forecasting; Employment forecasting